LINGUISTIC ASPECTS OF THE TRANSLATION OF MEMOIR WORKS (Journal of Universal Science Research, 2023)
A memoir is a non-fiction story written from the author's point of view, recounting and reflecting on a particular event or series of events in his or her life. These events are usually important turning points in the author's life, leading to some kind of personal discovery that changed the direction of his life or his view of the world. Essentially, memoirs are excerpts from the author's own life that are retold with the intention of making the memoir as true and factual as possible. In this article, the linguistic and cultural aspects of the translation of memoirs are considered on the example of James David Vance's "A Memoir of a Family and Culture in Crisis".